Association of modifiable factors with the development of physical fitness of Austrian primary school children: A 4-year longitudinal study. Issue 8 (18th April 2022) - Ruedl, G; Niedermeier, M; Posch, M; Kirschner, W; Wirnitzer, K; Cocca, A; Greier, K
ABSTRACT: Physical fitness (PF) shows favourable associations with several health indicators in children. Children's PF depends on a variety of non-modifiable (e.g., sex and age) and modifiable factors (e.g., weight status and sports participation). The aim of this study was to evaluate the impact of modifiable and non-modifiable factors on the development of PF during the 4 years of primary school. A longitudinal study was carried out with 265 children. PF was assessed using the German Motor Performance Test 6–18, whereas modifiable and non-modifiable factors with parent's and children's questionnaires. Total PF z‐score increased by 1.4 standard deviations from 1 st to 4 th year and raw values of subtests improved by an average of about 40%. The variables "parents' physical activity", "never being overweight", "sports club participation", and "playing outside" were positively associated with PF development. The present study highlights that a variety of modifiable factors, both from children and their parents, are significantly associated with the development of children's PF during primary education. Interventions should not only focus on direct actions, such as proposing specific exercise programs, but also aim at increasing parents' awareness of their role model function in endorsing their children's healthy active lifestyle, especially at early ages.